Manajemen Pengetahuan dan Pembelajaran Organisasi di Era VUCA; Studi Literatur - Nurul Fitria; Nizam Ulul Azmy; Mochammad Isa Anshori (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In the current business environment, knowledge management and organizational learning are one of the important aspects of a company. A company needs to have knowledge management and organizational learning like in the current VUCA era to improve the quality of the company. This research aims to find out how important knowledge management and organizational learning are to a company in the VUCA Era. This research methodology uses qualitative research, with the research method used is the literature study method. The data sources used are the results of various literature reviews such as scientific journals and articles on organizational learning and knowledge management. The results of this research show that knowledge management and organizational learning have an influence on the company, both in improving the company's performance and career and the performance of its employees' career funds.